The Measurement of the Impact of Housing on Happiness & Well-being - Hickson, Jason (2009)
Internship project for Blueprint Regeneration researching the feasibility of measuring the success of housing projects, particularly social housing developments, in terms of improving the happiness & wellbeing of the residents.